Problems and prospects of Russian tertiary education - V. M. Novikova (Vestnik MGIMO-Universiteta)
The article analyses main problems of Russian tertiary education including its international dimension and specific national characteristics. The author suggests possible ways of solving these challenges in order to improve the quality of education in this country, and evaluates prospects of Russian universities to become leaders in providing educational services.